Influence of Mn doping on the magnetic properties of CoFe2O 4 - Roongtao, Rachanusorn; Baitahe, Rattanai; Vittayakorn, Naratip; Seeharaj, Panpailin; Vittayakorn, Wanwilai C. (My University, 2014)
A series of CoFe2-xMnxO4 ceramics were synthesized successfully by conventional solid state reaction. The X-ray diffraction analysis proved that all samples were found to have a cubic spinel structure. Diffractograms were used for Rietveld refinement to determine lattice parameters, of which lattice parameter increased with increasing Mn concentration. The microstructure of the samples was studied using scanning electron microscopy. The vibrating sample magnetometer measurements showed that the highest saturated magnetization of 118.11 emu/g and coercivity of 46.89 Oe were observed in CoFe1.85Mn0.15O4 ceramic. Furthermore, X-ray absorption spectra of the samples were recorded to determine the Co, Fe and Mn valence states and their preferentially sites of the spinel structure. © 2014 Taylor and Francis Group, LLC.
Keywords: Cobalt ferrite; magnetic properties; manganese doping; XANES spectra